Public Health Emergency Response Lessons Learned by Rapid Deployment Force 3, 2006–2016 - Iskander, John (Am J Public Health, 2018)
Following Hurricane Katrina, the uniformed US Public Health Service created an updated system through which its officers participated in emergency responses. The Rapid Deployment Force (RDF) concept, begun in 2006, involved five teams of officers with diverse clinical and public health skill sets organized into an incident command system led by a team commander. Each team can deploy within 12 hours, according to a defined but flexible schedule. The core RDF mission is to set up and provide care for up to 250 patients, primarily persons with chronic diseases or disabilities, in a temporary federal medical station. Between 2006 and 2016, the RDF 3 team deployed multiple times in response to natural disasters and public health emergencies. Notable responses included Hurricane Sandy in 2012, the unaccompanied children mission in 2014, and the Louisiana floods in 2016. Lessons learned from the RDF 3 experience include the need for both clinical and public health capacity, the value of having special mental health resources, the benefits of collaboration with other federal medical responders, and recognition of the large burden of chronic disease management issues following natural disasters.